Cross-tolerance Responses of Gamma Co60 Irradiation-derived Sugarcane Mutants to Salinity and Osmotic Stress Under In Vitro Conditions - Gieks Sugiyono; Annaasta Tria Nur Alpyan; Nesya Diana Prameswari Putri; Siti Samiyarsih; Paul A. Davison; Rendie Prasetyo (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2026)
Sugarcane (Saccharum officinarum L.) cultivation is increasingly expanding into marginal lands affected by salinity and drought stress, requiring the development of stress-tolerant cultivars. This study aimed to evaluate the cross-tolerance responses of gamma irradiation-derived sugarcane mutants to salinity and osmotic stress under in vitro conditions. The experiment was arranged in a split-plot design with three replications. The main plot consisted of two putative mutant clones (11.201 and 11.401) and one wild-type clone (11.000) of sugarcane cultivar NXI 1–3. Salinity stress was induced using NaCl concentrations of 0, 50, 100, 150, 200, and 250 mM, while osmotic stress was induced using polyethylene glycol (PEG) concentrations of 0, 5, 10, 15, 20, and 25%. Observed parameters included explant survival percentage and the numbers of shoots, leaves, and roots. Both NaCl and PEG treatments significantly reduced microshoot growth. However, clone 11.201 consistently showed better survival and growth performance under both stress conditions compared with the wild type and clone 11.401. Clone 11.201 maintained its growth under 200 mM NaCl, yielding an average of 33.67 ± 13.58 shoots/explant, 143.00 ± 61.51 leaves/explant, and 2.33 ± 2.08 roots/explant. It also exhibited limited leaf production at 15% PEG (3.33 ± 5.77 leaves/explant. The results indicate the potential occurrence of cross-tolerance associated with gamma irradiation-induced variation.